PENGARUH BIG FIVE PERSONALITY TERHADAP KETERIKATAN KARIR DENGAN ADAPTABILITAS KARIR SEBAGAI PEMEDIASI PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Raisunnisa Raisunnisa; Megawati Megawati (Jurnal Manajemen Inovasi, 2019)
This study aims to measure the effect of Big Five Personality to undergraduate student’s Career Engagement in Economic and Business Faculty of Syiah Kuala University with Career Adaptability as mediating variable. The sample used in this study were active undergraduate students in odd semester 2018/2019 is totaling 240 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Proportionated Stratified Random Sampling. Hierarchical Linear Modelling (HLM) is used as a method of analysis to determine the effect of all the variables involved. Based on the result of the HLM analysis indicated that each Big Five Personality (i.e Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) positively influence Career Engagement and Career Adaptability, Career Adaptability positively influence Career Engagement and mediates the relationship between each Big five personality (i.e Openness, Conscientiousness, Extraversion, Agreeableness,Neuroticism) and Career Engagement.Keywords Career Engagement, Big Five Personality, Career Adaptability, Hierarchical Linear Modelling